Modeled Impacts of LULC and Climate Change Predictions on the Hydrologic Regime in Belize - Martín-Arias, Vanesa; Evans, Christine; Griffin, Robert; Cherrington, Emil A.; Lee, Christine M.; Mishra, Deepak R.; Gomez, Nicole Auil; Rosado, Andria; Callejas, Ileana A.; Jay, Jennifer A.; Rosado, Samir (Frontiers in Environmental Science, 2022)
Land use and land cover (LULC) change can have detrimental effects on water quality. In Belize, agricultural expansion creates the risk of increased sediment load and excess nutrients in runoff water, while deforestation removes potential infiltration sites for this outflow. Climate change and evolving precipitation rates can intensify the quantity of runoff, further enabling the flow of sediments and excess nutrients out to the lagoon surrounding the Belize Barrier Reef Reserve System (BBRRS). This study sought to estimate potential impacts on future water quality in Belize by first modeling LULC change through 2090 across Belize’s major watersheds based on observed trends from 2008-2018. Those LULC projections were subsequently combined with soil type data, elevation, and precipitation rates into a hydrologic model to produce runoff flow estimates as a proxy for water quality. The two Coupled Model Intercomparison Project phase 6 (CMIP-6) scenarios employed in the study represented bookend climate change scenarios, and both indicated generally lower precipitation rates in Belize over the next century due to climate change. The most extreme scenario predicted a 46% decrease in precipitation. When holding LULC change constant, these climate scenarios projected a decrease in runoff, suggesting a positive relationship between precipitation and runoff. In contrast with the northern watersheds, the southern watersheds are projected to experience greater decreases in annual rainfall and runoff by 2090. When holding climate constant, runoff increased by approximately 2.8% in the Conservation-focused LULC scenario by 2090, which was 28% lower than the Business as Usual scenario and 42% lower than the Development scenario. The study’s integration of CMIP6 climate scenarios into LULC and hydrologic modeling provides a more holistic view of the future of Belize’s water quality and supports the long-term planning efforts of local decision-making agencies.